Ultrahigh-ductility cement-based composite material for ocean engineering and preparation method thereof

By using ultra-high ductility cement matrix composite materials in marine engineering buildings, combining low permeability siliceous aggregates, organic synthetic fibers and new organic rust resistors, the problems of insufficient permeability, corrosion resistance and durability of high ductility concrete in marine environments are solved, and higher structural performance and safety are achieved.

CN119638346AActive Publication Date: 2025-03-18CCCC FOURTH HARBOR ENG CO LTD +1

Patent Information

Application Number
CN202411953411.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

In marine engineering buildings, medium and high-ductile concrete faces insufficient permeability, corrosion resistance and durability in marine service environments. Especially in high temperature, high humidity and high salinity environments, steel bars and concrete are easily corroded by chloride, resulting in reduced structural performance and safety hazards.

Method used

Using an ultra-high ductility cement-based composite material for marine engineering, the use of low permeability siliceous aggregates such as fly ash, silica fume, slag powder, metakaolin, and incorporate organic synthetic fibers and new organic rust resistors to improve the integrity, density and interface binding force of concrete, reduce the diffusion of chloride ions, and prevent corrosion through chemical bonding and electrostatic adsorption.

Benefits of technology

It significantly improves the permeability, corrosion resistance and durability of concrete, extends the service life of steel bars, enhances the fatigue and impact resistance of concrete, and ensures the safety and structural stability of marine engineering buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638346A_ABST
    Figure CN119638346A_ABST
Patent Text Reader

Abstract

The invention provides an ultrahigh-ductility cement-based composite material for ocean engineering and a preparation method of the ultrahigh-ductility cement-based composite material for ocean engineering. The concrete is prepared from the following raw materials in parts by weight: 250 to 500 parts of cement clinker, 400 to 600 parts of fly ash, 200 to 300 parts of mineral powder, 100 to 150 parts of silica fume, 160 to 240 parts of metakaolin, 600 to 900 parts of quartz sand, 10 to 20 parts of organic synthetic fiber, 20 to 30 parts of organic corrosion inhibitor, 180 to 240 parts of water and 1 to 8 parts of water reducing agent. The organic corrosion inhibitor provided by the invention can be combined with chloride ions to form a passive film, so that the corrosion of reinforcing steel bars and the invasion of the chloride ions into concrete are inhibited, and the durability of the concrete is improved; by regulating and controlling the mixing ratio of the four mineral admixtures and the mixing amount of the synthetic fiber component, the concrete can well consider high strength, high ductility, high durability, high flow state and excellent deformation resistance. The ultrahigh-ductility concrete for ocean engineering, which can meet the toughness requirements of high compression resistance, fracture resistance and impact resistance and the requirements of high chloride ion permeation resistance and steel bar corrosion resistance, can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to an ultra-high ductility cement-based composite material for marine engineering and a preparation method thereof. Background Art

[0002] High ductility concrete (HDC), also known as engineered cementitious composites (ECC), is a high-performance fiber-reinforced cementitious material with multi-crack characteristics, strain hardening characteristics, and excellent crack control capabilities. When subjected to bending and tensile loads, due to the bridging effect of the fibers, the cracks can stably expand and show obvious multi-crack characteristics and strain hardening behavior. Based on these characteristics, high ductility concrete has become a new research hotspot. As a structural material, functional gradient material, and repair and reinforcement material, it can be used in concrete structures with high toughness and durability requirements, such as earthquake-resistant structures, shotcrete supports, roads, railways, ports, and docks.

[0003] The preparation of high-ductility large-volume concrete in marine engineering construction applications usually selects materials such as high-strength steel bars, high-performance concrete and high-strength steel fibers. In the service environment of high temperature, high humidity and high salinity, metal materials such as steel bars and steel fibers are the first to suffer from the corrosion of chlorides and other harmful substances. The penetration of chlorides mainly relies on the diffusion effect of the chloride ion concentration difference in the capillary liquid of concrete. In the marine environment, high-concentration chloride ions diffuse from the marine environment into the concrete and penetrate into the surface of the steel bars under the action of concentration diffusion, forming chemical corrosion and electrochemical corrosion between the steel bars and concrete, destroying the passivation film on the surface of the steel bars, and causing a significant decrease in the surface state and mechanical properties of the steel. Under long-term service, the steel bars are corroded and damaged, and the internal stress concentration of the concrete causes local expansion. The bonding between the concrete and the steel bars is affected, resulting in concrete cracking. It may even threaten the safety of the engineering structure and induce safety accidents.

[0004] In addition, concrete structures are subjected to repeated wave loads and scouring in projects such as offshore platforms, so concrete is required to have good impact resistance and fatigue resistance. With the frequent occurrence of disasters such as earthquakes and typhoons, huge losses have been caused to infrastructure, which will place higher requirements on the toughness and durability of large-volume concrete structures of infrastructure. Summary of the invention

[0005] In order to solve the problem that the impermeability, corrosion resistance and durability of high-ductility concrete in marine service environment need to be improved, this section aims to provide an ultra-high ductility cement-based composite material for marine engineering and a preparation method thereof.

[0006] On the one hand, the present invention provides an ultra-high ductility cement-based composite material for marine engineering, which comprises the following raw materials, by weight: 250-500 parts of cement clinker, 400-600 parts of fly ash, 200-300 parts of mineral powder, 100-150 parts of silica fume, 160-240 parts of metakaolin, 600-900 parts of quartz sand, 10-20 parts of organic synthetic fiber, 20-30 parts of organic rust inhibitor, 180-240 parts of water, and 1-8 parts of water reducer;

[0007] The organic rust inhibitor has the following molecular structure:

[0008]

[0009] Furthermore, the cement clinker is one of sulphoaluminate cement and ordinary Portland cement, with a strength grade of 42.5 or above; the fly ash is Grade I fly ash, with a specific surface area of ​​≥350m 2 / kg; the silicon dioxide content in the silica ash is ≥92%; the mineral powder is S95 grade mineral powder, with a specific surface area of ​​≥400m 2 / kg; the metakaolin powder is obtained by calcining kaolin at 700-900°C for 2-4h and grinding it to a specific surface area of ​​>350m 2 / kg.

[0010] Fly ash, silica fume, slag powder and kaolin have a volcanic ash effect, which can promote the formation of more hydrated calcium silicate gel and enhance the bonding force between concrete particles; silica fume and kaolin are more active, which can quickly increase the density of concrete, improve impermeability, and greatly reduce the diffusion of chloride ions. Silica fume with lower density also plays a filling and lubricating role, optimizes the micropore structure, and reduces the porosity.

[0011] Furthermore, the quartz sand has a particle size of 100 to 200 meshes; the water reducer is a polycarboxylic acid water reducer, and the water reduction rate is ≥25%.

[0012] The difference from machine-made sand is that quartz sand itself has a certain activity and can be hydrated, which can further reduce the porosity between cement and aggregate and increase the density of concrete; quartz sand can also form crystallization centers, so that when cement is hydrated, it crystallizes around the quartz powder / sand and makes the crystals grow, thus improving the integrity of aggregate and cementitious materials and the mechanical properties of concrete.

[0013] Furthermore, the organic synthetic fiber is selected from at least one of polyvinyl alcohol (PVA) fiber, polypropylene (PP) fiber, polyethylene (PE) fiber, and polyoxymethylene (POM) fiber.

[0014] Organic synthetic fibers themselves have a certain tensile strength and modulus. They do not change the chemical properties and composition of other materials in concrete, greatly improving the ductility of concrete and obtaining better mechanical properties such as impermeability, crack resistance, tensile strength, and bending resistance. Synthetic fibers have good affinity and bonding with concrete, and are easily evenly distributed in concrete, enhancing interfacial bonding.

[0015] Furthermore, the organic rust inhibitor is obtained by: 1) substitution of N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine with cis-3,4-dichlorocyclobutene in the presence of an alkali reagent to obtain a product; 2) click reaction of the substitution product with DOTA-thiol under conditions of a photoinitiator and ultraviolet irradiation to obtain a product;

[0016] The reaction molar ratio of the N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine to cis-3,4-dichlorocyclobutene is 1:(2.01-2.2); the reaction molar ratio of the substitution product to DOTA-thiol is 1:(2.1-2.4).

[0017] Furthermore, the alkaline reagent is at least one of triethylamine, pyridine, N-diisopropylethylamine, sodium carbonate, and potassium carbonate, and the amount used is 1.05 to 1.2 times the molar amount of cis-3,4-dichlorocyclobutene; the photoinitiator is at least one of benzoin dimethyl ether, bis(dimethylaminonaphthalene), azobisisobutyronitrile, tert-butyl peroxide benzoyl and methyl ethyl ketone peroxide, and the amount used is 2 to 3 times the molar equivalent of the alkenyl group.

[0018] The present invention improves the performance of concrete for marine engineering from two aspects. First, by selecting low-permeability siliceous aggregate fly ash, silica fume, slag powder, and metakaolin, the integrity and density of concrete are improved, pores and defects are reduced, thereby reducing shrinkage cracking, reducing the penetration of water and salt, and improving the durability of concrete structure; adding organic synthetic fibers with high elastic modulus makes the fatigue resistance and impact resistance of concrete both; second, a new type of organic rust inhibitor is developed. On the one hand, the compatibility of its polar group with organic fibers and cementitious materials enhances the interface bonding force between concrete and synthetic fibers, and on the other hand, it plays a rust-proof role, can chemically combine with Fe ions in steel bars to produce a metal passivation protective layer, and can also combine with infiltrated anions through electrostatic adsorption, effectively preventing the migration of chloride ions and other harmful ions in the pore phase of concrete.

[0019] On the other hand, the present invention provides a method for preparing the above-mentioned ultra-high ductility cement-based composite material for marine engineering, comprising the following steps:

[0020] The cement, fly ash, silica fume, metakaolin and mineral powder in corresponding weight portions are measured and dry-mixed in a mixer for 2 to 3 minutes to obtain a mixed cementitious material; then the organic synthetic fiber is slowly added in batches along the mixing direction, and the dry-mixing is continued for 1 to 2 minutes; then water, a water reducing agent and an organic rust inhibitor are added, and wet-mixed for 2 to 5 minutes until the mortar mixture is fluid; the mortar mixture is poured and vibrated into shape, left to stand for 24 hours to demould, and standardly cured for 28 days to obtain ECC concrete.

[0021] In order to ensure uniform mixing of low-slump three-grade concrete, the mixing time of the mixer is set to be no less than 130s; during the concrete pouring process, the slump detection of concrete at the outlet and discharge port is strengthened, and the vibration status of concrete entering the warehouse is closely monitored to ensure that no floating slurry and water seepage appear after concrete is vibrated.

[0022] In the present invention, the stirring, grinding and roasting equipment used can be selected from existing equipment according to actual use conditions, and no special requirements are made on the equipment model.

[0023] The present invention also provides the use of the above-mentioned ultra-high ductility cement-based composite material for marine engineering in the outer protective layer of large-volume concrete of marine engineering.

[0024] Beneficial effects of the present invention:

[0025] In the present invention, the organic rust inhibitor used contains carboxylic acid, tertiary amine, secondary amine, nitrogen heterocycle, sulfur group, on the one hand, the amino group can be Cl - Electrostatic physical adsorption forms an adsorption layer on the surface of the steel bar, effectively preventing Cl - On the other hand, amino, sulfur and oxygen groups contain large lone pair electron density, which can form strong chemical adsorption with Fe atoms to form a dense passivation protective film. The double adsorption effect further inhibits the charge transfer during the corrosion process, improves the stability and density of the protective film on the surface of the steel bar, effectively inhibits metal corrosion, and improves the durability of concrete. In addition, the rust inhibitor molecules are highly hydrophilic and can quickly penetrate and diffuse into the surface of concrete or steel bars, inhibiting the corrosion of steel bars and concrete, and extending the service life and durability of high-ductility concrete steel bars used in large-volume construction of marine engineering.

[0026] In the present invention, the use of a large amount of mineral admixtures in the cementitious material realizes the secondary utilization of industrial waste fly ash, slag powder, silica fume, and kaolin on the one hand; on the other hand, it is conducive to the compactness and low porosity of the concrete, and improves the impermeability and crack resistance. The synthetic fiber component can be better combined with the cementitious material within the limited dosage range, so that the concrete can better balance high strength, high ductility, high fluidity, and excellent resistance to deformation and fatigue, and finally obtains ultra-high ductility mass concrete that can meet the high compression resistance, flexural resistance, impact toughness and other performance requirements for marine engineering construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the nuclear magnetic hydrogen spectrum of the organic rust inhibitor synthesized by the present invention. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0029] The sources and properties of the raw materials used are as follows:

[0030] 42.5 High Belite Sulphoaluminate Cement, provided by Tangshan Polar Bear Building Materials Co., Ltd., with the implementation standard of Q / TBJX25; its main technical indicators are shown in Table 1. Sulphoaluminate cement is a cement clinker with early strength, fast hardening, low alkalinity, slight expansion and self-stress, made of anhydrous calcium sulphoaluminate (C4A3S) and dicalcium silicate (C2S) as the main minerals and appropriate amounts of limestone and gypsum.

[0031] Table 1 Main technical indicators of ordinary sulphoaluminate cement

[0032]

[0033] PO 42.5R ordinary Portland cement is provided by China Resources Cement Holdings Co., Ltd. and is implemented in accordance with GB175-2007. Its main technical indicators are shown in Table 2. Ordinary Portland cement is a cement clinker made of mainly Portland cement clinker, mixed with active mixed materials and an appropriate amount of gypsum.

[0034] Table 2 Technical indicators of ordinary Portland cement

[0035]

[0036] Grade I fly ash, with a fineness (45μm sieve residue) of 8%, was provided by Guodian Shenzhen Energy Huayingshan Power Generation Co., Ltd.; S95 slag powder was alkali slag powder provided by Xiangtan Iron and Steel Co., Ltd. and Yangchun New Iron and Steel Co., Ltd.; silica fume, with a particle size of 0.17μm and a fineness (45μm sieve residue) of 3%, was provided by Guizhou Ferroalloy Plant. The technical indicators are shown in Table 3.

[0037] Table 3 Physical technical indicators of mineral powder, fly ash and silica fume

[0038]

[0039] Metakaolin is obtained by calcining kaolin at 850℃ for 3h. The specific surface area after grinding is 398m 2 / kg, and the average particle size is 15.32μm.

[0040] The chemical compositions of the four mineral admixtures are shown in Table 4.

[0041] Table 4 Chemical composition of mineral admixtures (wt.%)

[0042] raw material CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> MgO <![CDATA[P2O5]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> Loss Fly ash 3.35 49.26 20.14 14.33 0.72 / 1.79 0.67 9.74 Slag powder 37.55 32.94 9.13 3.07 9.54 / / / 7.77 Silica Fume 0.41 95.07 0.68 1.68 0.36 / / / 1.8 Metakaolin 0.17 55.87 36.12 1.04 0.34 0.25 0.21 0.77 5.23

[0043] Quartz sand, 80-120 mesh, silicon dioxide content 99.5%, Mohs hardness 7, provided by Shitouyuan Building Materials Store, Nanhai District, Foshan City. Its main technical indicators are shown in Table 5.

[0044] Table 5 Technical indicators of quartz sand

[0045] raw material <![CDATA[Apparent density (kg / m 3 )]]> <![CDATA[Bulk density (kg / m 3 )]]> Water absorption (%) <![CDATA[Cl - Content (%)]]> Mud content (%) Quartz sand 2568 1106 5.2 0.053 0.21

[0046] DUK-8PVA fiber, with a diameter of 15 μm, a length of 9 mm, a tensile strength of 1990 MPa, an elongation at break of 4-8%, and an elastic modulus of 3.5 GPa, was provided by Guangdong Zhongtian Port Bridge Construction Engineering Co., Ltd.

[0047] PE monofilament staple fiber, with a diameter of 15 μm, a length of 9 mm, a tensile strength of 390 MPa, an elongation at break of 3.5-3.75%, and an elastic modulus of 5.1 GPa, was provided by Shandong Haosen Construction Engineering Co., Ltd.

[0048] HY-453PP monofilament staple fiber, diameter 18μm, length 9mm, tensile strength 570Mpa, elongation at break 15-20%, elastic modulus 4.3GPa, moisture absorption rate <0.1%, provided by Shandong Hongyao Copper Materials Co., Ltd.

[0049] POM monofilament staple fiber, diameter 37 μm, length 9 mm, tensile strength 1000 MPa, elongation at break 30%, elastic modulus 15 GPa, moisture absorption rate <0.1%, provided by Shanghai Shenxiang Concrete Fiber Co., Ltd.

[0050] PVA fiber is non-toxic, non-polluting, has good sunlight resistance, good resistance to acidic and alkaline environments, and is suitable for a variety of concrete use environments. It can not only improve the frost resistance, wear resistance and carbonization resistance of concrete

[0051] PP and PE fibers have low density, are insoluble in water, and have good acid, alkali and salt corrosion resistance; POM fibers inherit the high strength and modulus, resistance to organic solvents and salt solutions, strong alkali corrosion and weathering properties of conventional copolymer formaldehyde, and have strong resistance to alkaline solutions, seawater and solvents.

[0052] Polycarboxylate water reducer, Sika (China) Co., Ltd., specific technical indicators are shown in Table 6.

[0053] Table 6 Technical indicators of polycarboxylate water reducer

[0054]

[0055] In some embodiments of the present invention, the rust inhibitor used is synthesized by the following steps:

[0056] 1) Add 120mL of dichloromethane to a 250mL round-bottom flask equipped with a constant pressure dropping funnel and magnetic stirring and place it in a 0℃ constant temperature bath, add 0.05mol of N,N,N',N'-tetra(2-hydroxypropyl)ethylenediamine and 0.12mol of triethylamine, stir thoroughly, and then slowly drop 40mL of dichloromethane solution containing 0.12mol of cis-3,4-dichlorocyclobutene into the flask within 1h; the mixture is stirred and reacted at 0℃ for 9h. After the reaction is completed, dichloromethane is added to dilute, filter, and repeatedly wash with saturated sodium chloride solution and deionized water until the organic phase is neutral, separate and collect the organic phase, transform with anhydrous magnesium sulfate for 24h, filter, and evaporate dichloromethane, and separate and purify the crude product with a silica gel column to obtain 167g of the substituted product with a yield of 85.2%.

[0057] 2) Add 0.02mol of the substituted product, 0.45mmol DOTA-thiol, and 150mL of anhydrous DMAc to a 500mL beaker with a mechanical stirrer, mix well, add 0.04mmol 1,8-bis(dimethylaminonaphthalene) as a catalyst, and stir to dissolve; irradiate the mixture at room temperature for 20min under a UV lamp (Intelli-Ray 600 UV curing box, UV lamp irradiation distance 15cm) to obtain a viscous mixture; after vacuum removal of DMAc, precipitate the mixture in 10 times the volume of ether to remove unreacted reactants and catalysts; the precipitate is vacuum dried at 60°C for 24h to obtain a rust inhibitor with a yield of 96.6%. The rust inhibitor molecule was tested using the AVANCE superconducting nuclear magnetic resonance spectrometer of the German Bruker company for the nuclear magnetic hydrogen spectrum (400MHz, deuterated chloroform), and the results are shown in Figure 1 .

[0058] Examples 1 to 12

[0059] Examples 1 to 12 provide an ultra-high ductility cement-based composite material for marine engineering, and the weight proportions of the raw materials used are shown in Table 7. Among them, the amount of water in Examples 1 to 4 increases synchronously with the amount of cement to control the same water-cement ratio; the type of cement in Examples 1 to 11 is ordinary sulphoaluminate cement, and the type of cement in Example 12 is ordinary Portland cement.

[0060] Table 7 Ratio of raw materials used in ultra-high ductility cement-based composite materials for marine engineering (by weight)

[0061]

[0062] According to the amounts shown in Table 7, cement, fly ash, silica fume, metakaolin and mineral powder in corresponding weight portions are measured in turn and dry-mixed in a mixer for 2 to 3 minutes to obtain a mixed cementitious material; then, organic synthetic fibers are slowly added in batches along the mixing direction, and dry-mixing is continued for 1 to 2 minutes; then, water, water reducing agent and organic rust inhibitor are added, and wet-mixing is performed for 3 to 5 minutes until the mortar mixture is fluid; the mortar mixture is poured and vibrated into shape, left to stand for 24 hours to demould, and standard curing is performed for 28 days to obtain high ductility concrete.

[0063] Comparative Examples 1-2

[0064] The rust inhibitor provided by the present invention was replaced by commercially available CPA anti-corrosion agent (purchased from Guangdong Jinlida Materials Technology Co., Ltd.) and KFS-1 anti-corrosion agent (purchased from Guangxi Hengyong Building Materials Co., Ltd.), respectively, and other conditions were the same as those in Example 2 to obtain high ductility concrete.

[0065] Among them, CPA anti-corrosion enhancer is an organic quaternary ammonium salt organic rust inhibitor, off-white powder, total alkali content <0.4%; KFS-1 concrete anti-corrosion agent is a rust inhibitor prepared by surfactant, inorganic salt and organic additive. The technical indicators of the two are shown in Table 8, and the implementation standard is GB / T23439-2017 "Concrete Expansion Agent".

[0066] Table 8 Technical indicators of two commercially available rust inhibitors

[0067]

[0068] Comparative Example 3

[0069] The difference from Example 2 is that the weight portion of the rust inhibitor used is reduced to 10 parts.

[0070] Comparative Examples 4-5

[0071] The difference from Example 2 is that the synthetic fibers are 2 parts and 25 parts by weight respectively.

[0072] Relevant tests were performed on the concrete obtained from Examples 1 to 12 and Comparative Examples 1 to 5, and the test results are summarized in Table 9.

[0073] Tensile properties: Refer to JC / T 2461-2018 "Test Method for Mechanical Properties of High Ductility Fiber Reinforced Cement-based Composites", and use MTS10T universal material testing machine for testing. The specimen size is 100mm×100mm×100mm cube, the loading method is displacement controlled loading, and the loading rate is 0.2mm / min.

[0074] Equivalent bending strength, equivalent bending toughness, flexural strength and compressive strength: measured in accordance with the performance indicators in the Technical Specification for Application of High Ductility Concrete (DB62 / T 3159-2019). The compressive strength test specimens were 100mm×100mm×100mm cubic specimens with a loading speed of 1.2MPa / s; the cubic flexural strength test specimens were 100mm×100mm×400mm prism specimens with a loading speed of 0.2mm / min.

[0075] Resistance to chloride ion penetration: The test is carried out in accordance with the method for chloride ion penetration resistance test in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Concrete".

[0076] Steel bar corrosion rate: referring to JGJ / T192-2009 "Technical Specification for Application of Steel Bar Rust Inhibitors", Q235 steel bars with a diameter of 6mm and a length of 1.2cm were buried in concrete, and the molds were removed 72 hours after forming. After standard curing for 7 days, the concrete specimens were baked in an oven at 80°C for 24 hours, and after cooling to room temperature, they were placed in a chloride ion solution (prepared with 5% sodium chloride + 95% water) for corrosion test, and electricity was applied to accelerate the corrosion for 28 days; then the concrete was broken, the steel bars were taken out, the rusted steel bars in the bonding section were cut, the rust products were cleaned with hydrochloric acid, the cleaned steel bars were weighed, the rust loss mass was calculated, and the steel bar corrosion rate was deduced (corrosion rate = (mass of fixed length uncorroded steel bars - mass of steel bars with rust products removed) / mass of fixed length uncorroded steel bars × 100%).

[0077] Table 9 Test results of relevant properties of high ductility concrete

[0078]

[0079]

[0080] From the data in the above table, it can be seen that the performance indicators of the concrete in Comparative Examples 1 to 2 are all worse than those in Example 2. - In terms of permeability, the rust inhibitor provided by the present invention contains carboxylic acid, tertiary amine, nitrogen heterocycle, sulfur group, oxygen group and heterocycle, and has a better rust inhibition effect than the quaternary ammonium salt rust inhibitor of comparative example 1 and the inorganic rust inhibitor of comparative example 2. In addition, the mechanical properties are further optimized with the increase of the rust inhibitor dosage, because the rust inhibitor of the present invention has good affinity with synthetic organic fibers and cementitious materials, and can increase the binding force and integrity of fibers, concrete and rust inhibitors.

[0081] From Examples 1 to 4, the proportions of fly ash, mineral powder, silica fume, and kaolin have a certain influence on the crack resistance and corrosion resistance of concrete. On the one hand, silica fume has the lowest density and can fill micro-voids to improve the interface structure. Its smooth surface can reduce internal friction and increase the fluidity of the mixture. On the other hand, its volcanic ash activity is the highest, which is beneficial to the increase of the compressive strength of concrete within a certain dosage range. The silica and alumina contained in kaolin are easy to break bonds and bond to form a three-dimensional aluminosilicate gel in concrete, which helps to improve the compressive strength. However, the two are highly active. If the dosage is too much, the concrete will harden and form too quickly, and it is easy to produce stratification or defects, resulting in an increase in the voids between the granular materials, which is not conducive to the overall density and strength enhancement of the concrete. The silica fume dosage of Example 4 is close to 10%, and the kaolin dosage of Example 1 exceeds 15%, resulting in insufficient mechanical properties of the concrete. The mineral powder is wrapped on the surface of cement particles, which can play an isolating role and delay the mutual overlap of cement hydration products; fly ash is spherical particles with small specific surface area, small water absorption capacity, and weaker activity than the other three materials, which can also well regulate the hydration speed of concrete according to needs. Combining the above test results with the construction cost, the concrete obtained by the material ratio used in Example 2 has better comprehensive performance.

[0082] Comparing the results of Example 2, Examples 5 to 6 with Examples 4-5, within the range of synthetic fiber dosage limited by the present invention, increasing the amount of synthetic fiber can improve the toughness and ductility of concrete; good flexural and bending strength. Organic synthetic fibers have high strength, elastic modulus and moderate elongation at break, which can effectively inhibit plastic cracks and shrinkage of concrete, and improve the toughness and ductility of concrete. The amount of synthetic fiber in Example 4 is too little, the concrete is brittle and ductile, the cracks are large when it is destroyed, and the tensile toughness is low. The excessive amount of synthetic fiber and fiber agglomeration in Example 5 cause low fluidity and defects in concrete, and the compressive strength is significantly reduced. In terms of the preference of different synthetic fibers, Examples 2 and Examples 7 to 9 show that concrete doped with PVA and POM has higher toughness and corrosion resistance than concrete doped with PP and PE. This is because PP and PE have smaller modulus and density, and their surfaces are hydrophobic and easy to agglomerate and float. PVA fiber has good dispersion in water, is not easy to stick, and can be evenly distributed in concrete; POM fiber has good thermal stability and extremely low water absorption, and can be used stably for a long time in high temperature or hot water; it is not decomposed by microorganisms, does not absorb plankton in seawater, and does not grow mold.

[0083] By comparing Example 2 with Example 12, it is easier to obtain corrosion-resistant and high-ductility concrete using ordinary sulphoaluminate cement than ordinary Portland cement. Compared with ordinary Portland cement, ordinary sulphoaluminate cement does not contain tricalcium aluminate (C3A) and tricalcium silicate (C3S) that are susceptible to corrosion, and thus has better corrosion resistance. Sulphoaluminate cement also has frost resistance and high impermeability, has low requirements for production conditions and ambient temperature, and can also be produced in low-latitude areas or cold seasons.

[0084] The present invention reasonably controls the proportion of four admixtures to enhance the density of concrete by adjusting the formula; adjusts the ductility and toughness of concrete by adjusting the proportion of fibers; effectively improves the resistance of concrete to chloride ion erosion and steel bar corrosion by adding a multifunctional rust inhibitor, thereby ensuring the engineering quality of concrete and improving the durability and safety and reliability of buildings. The present invention can be promoted and applied in the outer protective layer of marine engineering projects.

[0085] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. An ultra-high ductility cement-based composite material for marine engineering, characterized in that: The raw materials include, by weight: 250-500 parts of cement clinker, 400-600 parts of fly ash, 200-300 parts of mineral powder, 100-150 parts of silica fume, 160-240 parts of metakaolin, 600-900 parts of quartz sand, 10-20 parts of organic synthetic fiber, 20-30 parts of organic rust inhibitor, 180-240 parts of water, and 1-8 parts of water reducing agent. The organic rust inhibitor has the following molecular structure:

2. The ultra-high ductility cement-based composite material for marine engineering according to claim 1, characterized in that: The cement clinker is one of sulphoaluminate cement and ordinary silicate cement, with a strength grade of 42.5 or above; the fly ash is Grade I fly ash, with a specific surface area of ​​≥350m 2 / kg; the silicon dioxide content in the silica ash is ≥92%; the mineral powder is S95 grade mineral powder, with a specific surface area of ​​≥400m 2 / kg; the metakaolin powder is obtained by calcining kaolin at 700-900°C for 2-4h and grinding it to a specific surface area of ​​>350m 2 / kg.

3. The ultra-high ductility cement-based composite material for marine engineering according to claim 1, characterized in that: The quartz sand has a particle size of 80-200 meshes; the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥25%.

4. The ultra-high ductility cement-based composite material for marine engineering according to claim 1, characterized in that: The organic synthetic fiber is selected from at least one of polyvinyl alcohol fiber, polypropylene fiber, polyethylene fiber and polyoxymethylene fiber.

5. The ultra-high ductility cement-based composite material for marine engineering according to claim 1, characterized in that: The organic rust inhibitor is obtained by: 1) N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine and cis-3,4-dichlorocyclobutene in the presence of an alkali reagent to obtain a substitution product; 2) a click reaction between the substitution product and DOTA-thiol in the presence of a photoinitiator and ultraviolet radiation; The reaction molar ratio of the N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine to cis-3,4-dichlorocyclobutene is 1:(2.01-2.2); the reaction molar ratio of the substitution product to DOTA-thiol is 1:(2.1-2.4).

6. The ultra-high ductility cement-based composite material for marine engineering according to claim 5, characterized in that: The alkaline reagent is at least one of triethylamine, pyridine, N-diisopropylethylamine, sodium carbonate, and potassium carbonate, and the amount used is 1.01 to 1.2 times the molar amount of cis-3,4-dichlorocyclobutene; the photoinitiator is at least one of benzoin dimethyl ether, bis(dimethylaminonaphthalene), azobisisobutyronitrile, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide, and the amount used is 2 to 3 times the molar equivalent of the alkenyl group.

7. A method for preparing an ultra-high ductility cement-based composite material for marine engineering according to any one of claims 1 to 6, characterized in that: The following steps are involved: Take corresponding weight portions of cement, fly ash, silica fume, metakaolin and mineral powder and dry-mix them in a mixer for 2 to 3 minutes to obtain a mixed cementitious material; then slowly add organic synthetic fibers in batches along the stirring direction, and continue dry-mixing for 1 to 2 minutes; then add water, water reducing agent and organic rust inhibitor, and wet-mix for 3 to 5 minutes until the mortar mixture is fluid; pour and vibrate the mortar mixture into shape, let it stand for 24 hours to demould, and perform standard curing for 28 days to obtain high ductility concrete.

8. Use of the ultra-high ductility cement-based composite material for marine engineering as claimed in any one of claims 1 to 6 in the outer protective layer of large-volume concrete for marine engineering.

Citation Information

Patent Citations

  • Marine durable cement concrete

    CN101224968A

  • Preparation method of reinforced concrete corrosion inhibitor

    CN107759119A

  • C50-grade marine high-performance concrete

    CN111978036A

  • Ecological concrete and preparation method, and high-durability marine concrete structure construction method

    WO2021109994A1

  • Method for improving durability of cast-in-place concrete structure in tidal range zone of marine environment

    WO2023206972A1

Cited By

  • Dredged material environment-friendly geopolymer and preparation method thereof

    CN120518378A

  • Multifunctional seawater and sea sand ECC material based on ion reconstruction and internal and external source cooperative regulation and control and preparation method of multifunctional seawater and sea sand ECC material

    CN120554039A

  • Multifunctional seawater and sea sand ecc materials based on ion reconstitution and endogenous and exogenous synergistic regulation and preparation method thereof

    CN120554039B

  • Lithium slag-based salt corrosion resistant concrete pole and preparation method thereof

    CN121270212A